Rate of conversion of reports presented at the Turkish Society of Sports Traumatology, Arthroscopy and Knee Surgery Congress into publication - Murat Gulcek; Fatih Inci; Erman Ceyhan; Utku Gurhan; Yakup Kahve; Ahmet Ucaner (Acta Orthopaedica et Traumatologica Turcica, 2018)
Objective: The aim of this study was to evaluate the conversion rate of oral and poster presentations into publications presented at four consecutive congresses held by the Turkish Society of Sports Injuries and Arthroscopy between 2008 and 2014 and to determine the publication pattern. Methods: The manuscripts published in peer-reviewed journals were identified using the Web of Knowledge, PubMed, Google Scholar databases, ULAKBIM, and Endnote citation management software (X7.7.1). The identified manuscripts were classified according to the level of evidence, number of citations, subject, publication journals, time period until publication, and citation index of the journal. Results: Between 2008 and 2014, a total of 561 presentations were made, comprising 278 posters and 283 oral presentations. Of these presentations, 164 (29.2%) were published as a manuscript. Of the published articles, 114 were originated from oral presentations (40.2% of total) and 50 from poster presentations (18% of total). A significantly higher number of oral presentations compared to poster presentations were converted into publications (p < 0.05). However, no significant difference was determined between the conversion rates of oral and poster presentations in 2014. The mean time from presentation at the congress to publication was 15.4 months (range: −144 months to +62 months). The mean impact factor of the journals at the time of publication increased for each congress. Evidence level of presented articles was significantly higher in the 2014 congress when compared to previous congresses. Conclusion: The rate of conversion into publication was higher for oral presentations, which can be attributed to the fact that studies with a higher level of evidence are more likely to have been presented as oral presentations. Based on these study results, authors of oral presentations at congresses should be encouraged to increase the rate of conversion into publication. Keywords: Oral presentation, Poster presentation, Publication rate, TUSYAD Congress, Rate of conversion